Mandibulada asimetriye neden olan periferal osteoma: olgu sunumu ve literatür derlemesi - Huyla Erten; Benay Tokman; Defne Akpinar; Volkan Akar; Ceyda Kocabay; Zühre Zafersoy Akarslan (Cumhuriyet University, 2011)
The objective of this article is to describe the diagnosis and treatment of a peripheral osteoma, causing an asymetry on the posterior region of the mandible, and to review the present peripheral osteoma cases in the literature. A 52 year old female patient referred to our clinic for the treatment of a swelling localized on her left side of the posterior region of the mandible. After the clinical and radiographical examination, the prediagnosis of lesion was said to be a peripheral osteoma. The lesion was completely excised under local anesthesia and histological examination was performed. The final diagnosis of the lesion was made as a peripheral osteoma. As being rare, peripheral osteomas could be localized on the mandible and should be taken into account during differential diagnosis of other lesions causing asymmetry on the mandible.   ÖZET Bu makalenin amacı, mandibula posterior bölgesinde lokalize olup asimetriye neden olan bir periferal osteoma vakasının teşhis ve tedavisinin anlatılması ve literatürde rapor edilmiş olan vakaları incelemektir. 52 yaşında bir bayan hasta, mandibulasının sol posterior bölgesindeki şişliğin tedavisi amacı ile kliniğimize başvurdu. Yapılan klinik ve radyografik muayene sonucunda şişliğe sebep olan lezyonun ön tanısı osteoma olarak konuldu. Lezyonun tamamı, lokal anestezi altında eksize edilerek histolojik inceleme yapıldı. Lezyonun kesin tanısı periferal osteoma olarak kondu. Periferal osteomalar nadir de olsa mandibulada gelişebildiğinden, bu bölgede lokalize olan ve asimetri oluşturan diğer lezyonlardan ayırt edilmeleri gerekmektedir. Anahtar Kelimeler: mandibula, osteoma